The Effect of Ultrasound Therapy and Stretching on Pain Reduction in Carpal Tunnel Syndrome at Indramayu Regional Hospital - Usbatul Umamy; Sartoyo; Anis Ansyori; Nurul Halimah (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Carpal Tunnel Syndrome (CTS) is a compressive neuropathy caused by median nerve entrapment at the wrist, resulting in pain, numbness, tingling, and decreased hand function. These symptoms can interfere with daily activities and work productivity. Physiotherapy interventions play an important role in managing pain and improving functional outcomes in patients with Carpal Tunnel Syndrome. Ultra Sound Therapy is commonly used to reduce pain and inflammation through deep tissue heating and micro-massage effects, while Stretching Exercises aim to improve flexibility, reduce muscle tension, and decrease pressure within the carpal tunnel.Objective: To determine the effect of Ultra Sound Therapy combined with Stretching Exercises on pain reduction in patients with Carpal Tunnel Syndrome at RSUD Indramayu. Methods: This study used a pre-experimental design with a pretest–posttest one group approach. The subjects were patients diagnosed with Carpal Tunnel Syndrome who met the inclusion criteria. Pain intensity was measured using a standardized pain scale before and after the intervention. The intervention consisted of Ultra Sound Therapy followed by Stretching Exercises administered according to physiotherapy protocols. Data were analyzed using paired statistical tests to assess differences in pain intensity before and after treatment. Results: The results showed a significant reduction in pain intensity after the administration of Ultra Sound Therapy and Stretching Exercises compared to pre-intervention measurements (p < 0.05). Conclusion: The combination of Ultra Sound Therapy and Exercises has a significant effect in reducing pain in patients with Carpal Tunnel Syndrome. This intervention can be recommended as an effective physiotherapy modality for pain management in Carpal Tunnel Syndrome patients at clinical settings